Domestic Violence during Pregnancy among Postnatal Women in Tertiary Hospital, Nepal - Prajapati, Laxmi Maiya; Shrestha, Sarala (Nepal Journal of Multidisciplinary Research, 2022)
Domestic violence is the most prevalent pregnancy-related health issue in developing county. The health of both mother and child is seriously jeopardized. This research was to assess the incidence of psychological, physical, economical and sexual violence during pregnancy among postnatal mothers at Dhulikhel Hospital - Kathmandu University's Hospital. A descriptive cross-sectional study was conducted on 804 postnatal women. The respondents were chosen using a systematic random sampling strategy. Findings of the study revealed that the majority of respondents stated that they had little experienced psychological violence such as meeting restrictions, work obstruction, unjustified blaming, or threats during pregnant. The minority of responders indicate they have sometimes been slapped, pushed, yanked hair, burnt, attacked, or strangled by a family member while pregnant. Very few Respondents state that they have experienced sexual violence, such as being pushed or coerced to have sex when they are physically and mentally exhausted or have no interest. In that 36. % respondents experience tension during pregnancy due to domestic fights, 54.7% have faced such issue. Study show that domestic violence to pregnant women was seems .